2013
DOI: 10.1002/jrsm.1076
|View full text |Cite
|
Sign up to set email alerts
|

Less is less: a systematic review of graph use in meta‐analyses

Abstract: Graphs are an essential part of scientific communication. Complex datasets, of which meta-analyses are textbook examples, benefit the most from visualization. Although a number of graph options for meta-analyses exist, the extent to which these are used was hitherto unclear. A systematic review on graph use in meta-analyses in three disciplines (medicine, psychology, and business) and nine journals was conducted. Interdisciplinary differences, which are mirrored in the respective journals, were revealed, that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 38 publications
(49 reference statements)
0
31
0
Order By: Relevance
“…Forest plots are frequently used in meta-analyses to present the findings of the individual studies (Schild and Voracek, 2013). For each study, the plot shows the observed value of the outcome measure of interest (e.g., correlation coefficient) and the corresponding confidence interval (usually 95%) for the study's true outcome (Lewis and Clarke, 2001).…”
Section: Inference About Individual Studiesmentioning
confidence: 99%
“…Forest plots are frequently used in meta-analyses to present the findings of the individual studies (Schild and Voracek, 2013). For each study, the plot shows the observed value of the outcome measure of interest (e.g., correlation coefficient) and the corresponding confidence interval (usually 95%) for the study's true outcome (Lewis and Clarke, 2001).…”
Section: Inference About Individual Studiesmentioning
confidence: 99%
“…Graphs are an excellent way to represent data in a meta‐analysis (Anzures‐Cabrera and Higgins, ; Borenstein et al ., ). Despite the value of graphs for providing insight, several kinds of graphs are rarely used, and graphs are more likely to be used in medical journals than in social science journals, at least for psychology and business (Schild and Voracek, ). In their primer, Anzures‐Cabrera and Higgins () noted four main types of graphs used in meta‐analysis: forest plots, funnel plots, Galbraith plots, and L'Abbé plots.…”
Section: Graphs In Meta‐analysismentioning
confidence: 99%
“…In their primer, Anzures‐Cabrera and Higgins () noted four main types of graphs used in meta‐analysis: forest plots, funnel plots, Galbraith plots, and L'Abbé plots. Forest plots appear to be the most commonly published (Schild and Voracek, ).…”
Section: Graphs In Meta‐analysismentioning
confidence: 99%
“…This common design of forest plots has repeatedly been criticized (Barrowman and Myers, 2003;Jackson, 2008;Anzures-Cabrera and Higgins, 2010;Schriger et al, 2010;Schild and Voracek, 2013), and three points have been put forward: First, small studies may attract an undue amount of attention because of their long confidence intervals. Although small studies have less impact on the overall pooled result, they may appear more visually striking than larger ones.…”
Section: Design and Criticisms Of Conventional Forest Plotsmentioning
confidence: 99%